O FRAGMENTO EM TUTAMÉIA E NO LIVRO SOBRE NADA - Lima, Robeilza de Oliveira (2009)
This study is connected to the research line Poéticas da Modernidade e Pós -Modernidade, of the Programa de Pós-Graduação em Estudos da Linguagem, in the subarea: Comparative Literature - CCHLA/UFRN. Its main goal is to see fragmentation of writing as an aesthetic resource highlighted in the work of Tutaméia by Guimarães Rosa (1908-1967), and in Livro sobre nada by Manoel de Barros (1916). We undertake as a starting point the view that these works are allegorical expressions. We have as a basis the German philosopher Walter Benjamin (1984) conception about baroque allegory, that uses amorphous fragment and constitutes a dialectical expression, in which each person, each thing, each relation, may mean any other one (1984, p. 196). We see the stylistic features as used by Guimarães Rosa and by Manoel de Barros in the construction of poetics capable of breaking the boundaries between artistic genres, literary and discursive, adding oral, musical and plastic elements to writing. We also analyze the development of fragmentary poetics, in which the voice of the narrator/lyrical I, the characters, space, plot and time exhibit the fragment as a factor that contributes to the great ambiguity of the two works and to create a new language, performative and vibrant, rich in alluring images, allegories